2006
DOI: 10.1111/j.1600-6143.2006.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Versus Preemptive Oral Valganciclovir for the Management of Cytomegalovirus Infection in Adult Renal Transplant Recipients

Abstract: Prophylaxis reduces cytomegalovirus (CMV) disease, but is associated with increased costs and risks for side effects, viral resistance and late onset CMV disease. Preemptive therapy avoids drug costs but requires frequent monitoring and may not prevent complications of asymptomatic CMV replication. Kidney transplant recipients at risk for CMV (D+/R−, D+/R+, D−/R+) were randomized to prophylaxis (valganciclovir 900 mg q.d. for 100 days, n = 49) or preemptive therapy (900 mg b.i.d. for 21 days, n = 49) for CMV D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
302
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(325 citation statements)
references
References 29 publications
16
302
5
2
Order By: Relevance
“…A few randomized controlled trials have recently compared prophylaxis and preemptive therapy. However, Dþ/RÀ patients were not included (14) or represented only a minority of all patients included in these trials (10,11). Some studies showed a marked benefit of the preemptive approach in Dþ/RÀ patients (28,29), although recent studies have shown a similar or even higher incidence of CMV diseases compared to the use of antiviral prophylaxis (9,30).…”
Section: Impact Of CMV Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few randomized controlled trials have recently compared prophylaxis and preemptive therapy. However, Dþ/RÀ patients were not included (14) or represented only a minority of all patients included in these trials (10,11). Some studies showed a marked benefit of the preemptive approach in Dþ/RÀ patients (28,29), although recent studies have shown a similar or even higher incidence of CMV diseases compared to the use of antiviral prophylaxis (9,30).…”
Section: Impact Of CMV Preventionmentioning
confidence: 99%
“…Current guidelines recommend both approaches, although antiviral prophylaxis is generally preferred for high-risk patients (1,2). However, direct comparison of both strategies has been assessed only in a few small randomized controlled trials (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Because EOD occurs mainly after a preemptive strategy, we believe that this strategy is not appropriate in D+RÀ patients and argue strongly for universal prophylaxis in these high-risk patients. Moreover, in na€ ıve D+/RÀ patients, universal prophylaxis is thought to hamper the development of a specific immune response, causing more late-onset CMV infections than the preemptive approach (3,39), with increased morbidity (10). This observation could argue for the choice of a preemptive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…CMV incidence remains elevated in these patients, at between 16% and 37%, depending on the duration of preventive therapy (1,2). In one study directly comparing prophylactic and preemptive approaches, it was clearly demonstrated that late DNAemia occurs much more frequently in the prophylactic versus the preemptive setting (3,4). In addition, late DNAemia has been associated with poor prognosis, with a reduction in graft survival and higher patient mortality (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The patient may have benefited from a preemptive screening strategy, which has been recommended as an alternative to universal prophylaxis in kidney transplant recipients at risk for CMV infection [16,17]. While prophylaxis has been associated with superior graft and patient survival [18,19], as well as cost and quality of life benefits [20] compared to a preemptive strategy, the latter may be appropriate for patients at risk for CMV disease with contraindications to oral valganciclovir therapy [17,21].…”
Section: Discussionmentioning
confidence: 99%